The Representation of Sharia Values of BSI Tiktok Educational Videos in Maqasid Sharia Index Perspective - Indah, Tia Mardiana; Syahbudi, Muhammad (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This study examines the representation of sharia values in the educational video content of Bank Shariah Indonesia (BSI) on the TikTok platform, an increasingly influential medium for Islamic banking communication in the digital era. Using the Ash-Syatibi-based Maqasid Shariah Index (MSI) as an evaluation framework, 55 educational videos uploaded between January and December 2024 were analyzed through qualitative content analysis. Each video was assessed across the five MSI dimensions—hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal—using a 25-indicator rubric. The results show an overall MSI score of 2.695 (medium category), with hifz al-aql scoring the highest (3.30) and hifz al-nasl the lowest (2.44). These findings indicate that BSI has integrated sharia values fairly well into its digital communication strategy, although improvements are needed in content that supports family-related financial planning. This study contributes to the literature on Islamic banking communication by offering a systematic measurement model for evaluating sharia value representation in short-form social media content, and provides practical recommendations for enhancing sharia compliance in digital outreach.